Multimedia Glosses and the Cognitive Process in EFL Learning: A Study at SMP Negeri 2 Tiakur - Kamanasa, Louisa Sarah; Julianus, Jeni; Lekawael, Rosina F. J. (Koli Journal : English Language Education, 2025)
Vocabulary acquisition is a cornerstone in language learning, particularly for English as a Foreign Language (EFL) students, where proficient vocabulary knowledge underpins comprehension and communication skills. This study investigates the efficacy of multimedia glosses in enhancing vocabulary learning and retention among EFL learners of SMP Negeri 2 Tiakur, Southwest Maluku Regency, addressing the limitations of traditional methods in supporting vocabulary acquisition. Drawing from the literature on language acquisition and educational technology, the study employs an experimental design to compare the effectiveness of multimedia glosses against traditional approaches. Twelve male and fifteen female junior high school students of SMP Negeri 2 Tiakur participated and were divided into control and treatment groups. Results indicate a statistically significant advantage for the treatment group, demonstrating enhanced vocabulary learning outcomes. Moreover, the study explores the nuanced effects of multimedia glosses on vocabulary acquisition tasks, shedding light on the cognitive processes involved. Findings underscore the potential of multimedia glosses in facilitating vocabulary acquisition and comprehension among EFL learners, offering insights for educators and curriculum designers. This research contributes to the discourse on language learning methodologies and underscores the importance of leveraging technology to address pedagogical challenges in language education.